Gender attitudes and violence against women - York, Melinda R., 1980- (Criminal justice (LFB Scholarly Publishing LLC), 2011)
York seeks to answer the question of the extent to which traditional beliefs about gender or gender roles are associated with increased levels of sexual assault and/or domestic violence. She also investigates the extent to which social capital serves as a protective factor with respect to the safety of women. The prevalence of traditional gender attitudes predicted rates of violence against women, specifically sexual assault and domestic violence, while social capital serves as a mitigating factor. In counties with less social capital and more traditional gender attitudes, there were substanti.